Impact of Corporate Social Responsibility, Green Credit and Digitalisation on Bank Stability: A Case Study of Banks in Vietnam - Do Thi Mong Thuong; Phan Thi Hang Nga (Ianna Journal of Interdisciplinary Studies)
Background: Social responsibility, green lending, and digital transformation are crucial to sustainable development and offer banks chances to increase their market competitiveness and operate sustainably. Moreover, green credit and digital transformation are inevitable, but coordination is needed between banks, the government, and related organizations to implement them successfully.